PENGARUH RASIO PROFITABILITAS DAN RASIO PASAR TERHADAP HARGA SAHAM: - - Retnaningdiah, Dian -; Rianti (Program Studi Manajemen, 2024)
ABSTRACT Background: One of the goals of opening a business is to make a profit. The level of profitability plays a vital role in a company. If a company can make a high profit, then this can attract investors to invest in the company. Aim of the Study: This study aims to see the effect of the Profitability Ratio and Market Ratio on Stock Price. Research Method: This quantitative research uses a documentation method that is measured partially and simultaneously with the population of Healthcare companies listed on the IDX from 2020 to 2023. Sampling is based on the population using the Non-Probability Sampling technique with the purposive sampling method. Findings: The results obtained indicate that the Profitability Ratio (X1) does not affect Stock Price (Y), while the Market Ratio (X2) has a significant positive effect on Stock Price (Y). Profitability Ratio (X1) and Market Ratio (X2) have a simultaneous effect on Stock Price (Y). Conclusion: The results of this study can conclude that (1) Profitability Ratio (X1) does not have a partial effect on Stock Price (Y), (2) Market Ratio (X2) has a positive and significant partial effect on Stock Price (Y), (3) Profitability Ratio (X1) and Market Ratio (X2) have a simultaneous effect on Stock Price (Y) Keywords : Profitability Ratio, Market Ratio, Stock Price